Brand Loyalty SMP Negeri 1 Lumajang Pasca Penghapusan Rintisan Sekolah Bertaraf Internasional - Yusuf Wijanarko; Andi Sularso (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2014)
Developing school that has fulfilled all Educational National Standard (SNP) and enriched with specific high quality adopted from developed countries (SNP + X) is an application model of Pilot Internatioanl Standard School (RSBI). It is actually an alternative strategy for a better educational improvement. However, some problems and critics then appeared and came to accusation. Finally, this program was dissoluted. Primary, product of a school is an educational service. School must be customers satisfaction oriented. Before the dissolution of RSBI, SMPN 1 Lumajang commits to realize the branding of RSBI. As the effect of RSBI dissolution, SMPN 1 Lumajang still committed to maintain its brand loyalty by maintaining the service in ccordance with National Standard of Education (SNP), just by eliminating the international dimensions. After the dissolution, parents and students of grade 8 evaluate the decrease of the service quality, the decrease of customer satisfaction, but it doesn’t make the decrease of brand loyalty. Parents and students understand the decrease, the condition of fund, and their position of free for school-fee. Parents still hope that the quality of sercice will be better increased although they will pay for it. Some operational principles and steps can be taken by SMPN 1 Lumajang in maintaining brand loyalty after the dissolution of RSBI, as follow: (1) school has vivid vision and mission, (2) school holds on commitment to serve best, (3) schools keeps strong leadership, (4) school keeps effective teamwork, (5) school keeps effective teachers and staffs, (6) school put the School Committee as partner and mediator to parents, society and stakeholder, (7) school keeps the participation of whole school community, parents, society and stakeholder, (8) school keeps quality culture, (9) school has authority and independency, (10) school always has willingness to change, (11) school keeps effective communication, (12) school must be responsive and anticipative to the needs, (13) school has transparency and accountability, (14) school keeps the continuation teaching learning process effectively and conducive environment, (15) school uses and informs service excellences, (16) school creates differential on educational services, (17) school always keeps trust of students and parents, (18) school gives respond on complains seriously and takes responsible actions, (19) school guarantees the quality of education in accordance with hope, (20) school manages supervision, monitoring, evaluation and follow them up sustainably, and (21) school confirms brand loyalty. The government should also facilitate the law that eks-RSBI school is allowed to get some contribution from parents to support education fund.